E-lifestyle, Customer Satisfaction and Loyalty among Mobile Subscribers in Thailand - Hassan, Siti Hasnah; Thurasamy, T. Ramayah; Loi, Wai Yee (International Review of Management and Marketing, 2017)
This paper aims at assessing the relationship between e-lifestyle, customer satisfaction, and loyalty among mobile service subscribers in Thailand. The results reveal that e-lifestyle has a substantial effect on customer satisfaction. Subsequently, customer satisfaction affects strongly on consumer loyalty towards telecommunication service providers. Moreover, customer satisfaction mediates the relationship between e-lifestyle and consumer loyalty. The study concludes that e-lifestyle has to be integrated into marketing strategies and customer relationship management in order to sustain consumer loyalty. From a practical point of view, the findings of this study could be used to inform businesses, particularly those in the telecommunication services industry in developing countries on the ways of enhancing customer satisfaction and loyalty. Keywords: Customer Satisfaction, E-lifestyle, Loyalty. JEL Classifications: M30, M31, M37